Persons With Multiple Disabilities Engage in Stimulus Choice and Postural Control With the Support of a Technology-Aided Program. (May 2015) - Lancioni, Giulio E.; Singh, Nirbhay N.; O'Reilly, Mark F.; Sigafoos, Jeff; Perilli, Viviana; Campodonico, Francesca; Marchiani, Paola; Lang, Russell
Technology-aided programs have been reported to help persons with disabilities develop adaptive responding and control problem behavior/posture. This study assessed one such program in which choice of stimulus events was used as adaptive responding for three adults with multiple disabilities. A computer system presented the participants stimulus samples. For each sample, they could perform a choice response (gaining access to the related stimulus whose length they could extend) or abstain from responding (making the system proceed to the next sample). Once choice responding had strengthened, the program also targeted the participants' problem posture (i.e., head and trunk forward bending). The stimulus exposure gained with a choice response was interrupted if the problem posture occurred. All three participants successfully (a) managed choice responses and access to preferred stimuli and (b) gained postural control (i.e., reducing the problem posture to very low levels). The practical implications of those results are discussed.